PERAN DUKUNGAN SOSIAL DIGITAL MELALUI MEDIA SOSIAL TERHADAP KESEHATAN MENTAL MAHASISWA GENERASI Z - Fransisca Huang; Rostiana Rostiana (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The rapid development of social media has given rise to digital social support, which is increasingly utilized by Generation Z as active users of online platforms. This study examines the effect of digital social support on the mental health of Generation Z by adopting the digital social support theory proposed by Nick et al. (2018) and the three-dimensional mental health framework by Keyes (2002). A non-experimental quantitative approach with a correlational design was employed, in which primary data were collected through the Online Social Support Scale (OSSS) and the Mental Health Continuum–Short Form (MHC-SF) questionnaires distributed online to 150 Generation Z university students in the Greater Jakarta area. The analysis included descriptive statistics, classical assumption tests, and simple linear regression, revealing a positive and significant effect of digital social support on mental health (R = 0.483; p < 0.001) with a contribution of 23.3%. These findings indicate that higher levels of digital social support are associated with better mental health quality, thereby confirming the crucial role of social media as a source of emotional, social, and psychological well-being for Generation Z students. ABSTRAK Perkembangan pesat media sosial telah memunculkan dukungan sosial digital yang semakin dimanfaatkan oleh generasi Z sebagai pengguna aktif platform daring. Penelitian ini menguji pengaruh dukungan sosial digital terhadap kesehatan mental generasi Z, dengan mengadopsi teori dukungan sosial digital dari Nick et al. (2018) serta kerangka kesehatan mental tiga dimensi menurut Keyes (2002). Pendekatan kuantitatif non-eksperimental berbasis desain korelasional diterapkan, di mana data primer dikumpulkan melalui kuesioner Online Social Support Scale (OSSS) dan Mental Health Continuum–Short Form (MHC-SF) yang disebar secara online kepada 150 mahasiswa generasi Z di Jabodetabek. Analisis mencakup uji deskriptif, asumsi klasik, serta regresi linear sederhana, yang mengungkap pengaruh positif dan signifikan dukungan sosial digital terhadap kesehatan mental (R = 0,483; p < 0,001) dengan kontribusi 23,3%. Temuan ini mengindikasikan bahwa tingginya dukungan sosial digital yang diperoleh individu berkorelasi dengan peningkatan kualitas kesehatan mental, sehingga menegaskan peran krusial media sosial sebagai sumber kesejahteraan emosional, sosial, dan psikologis bagi mahasiswa generasi Z.